2011
DOI: 10.4314/ajtcam.v8i5s.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sedative and Anticonvulsant Properties of Three Cameroonian Plants

Abstract: Millettia thonningii, Ocinum sanctum and Securitaca longepedunculaca are used in traditional medicine in Cameroon to treat epilepsy, insomnia and headaches. Animal models of epilepsy (maximal electroshock (MES), n-methyl-d-aspartate (NMDA), pentylenetetrazol (PTZ), isonicotinic hydrazide acid (INH), picrotoxine (PIC) and strychnine (STR)-induced convulsions or turning behavior were used to evaluate anticonvulsant activity while diazepam-induced sleep test was used to evaluate sedative activity of the plants. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The aqueous extract of the root exhibited anticonvulsant, anxiolytic and sedative activities against mice in a dose dependent manner (Adeyemi et al, 2010;Okomolo et al, 2011), suggesting that the plant extract may be used in the management of convulsion and psychosis.…”
Section: Anticonvulsant Sedative and Anxiolytic Propertiesmentioning
confidence: 99%
“…The aqueous extract of the root exhibited anticonvulsant, anxiolytic and sedative activities against mice in a dose dependent manner (Adeyemi et al, 2010;Okomolo et al, 2011), suggesting that the plant extract may be used in the management of convulsion and psychosis.…”
Section: Anticonvulsant Sedative and Anxiolytic Propertiesmentioning
confidence: 99%
“…Seizure severity was measured up to the point where the maximal effect was reached using the following stages: stage 1: fictive scratching; stage 2: tremors, head nodding; stage 3: forelimb clonus; stage 4: continuous rearing, falling; stage 5: tonic-clonic seizures with hind limb extension, stupor, or jumping. The percentages of deaths occurring in the GII group were taken as 100% [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, recent studies report leaf extracts from ethanolic and aqueous tulsi protects rats from stress-induced cardiovascular changes [48, 49]. Studies in animal models have further shown that the leaf extract of tulsi possesses anticonvulsant and anxiolytic activities [50, 51]. Several animal studies conducted over the past fifty years report that ingestion of tulsi leaves improves both glucose and lipid profiles in normal and diabetic-induced animal models [36, 38, 52–58].…”
Section: Introductionmentioning
confidence: 99%